Diversity awareness, diversity competency and access to healthcare for minority groups: perspectives of healthcare professionals in Croatia, Germany, Poland, and Slovenia - Mojca Ramšak; Marcin Orzechowski; Katarzyna Bielińska; Anna Chowaniec; Robert Doričić; Robert Doričić; Marianne Nowak; Tobias Skuban-Eiseler; Ivana Tutić Grokša; Paweł Łuków; Amir Muzur; Amir Muzur; et al. (Frontiers Media S.A., 2023)
IntroductionDue to cultural, language, or legal barriers, members of social minority groups face challenges in access to healthcare. Equality of healthcare provision can be achieved through raised diversity awareness and diversity competency of healthcare professionals. The aim of this research was to explore the experiences and attitudes of healthcare professionals toward the issue of social diversity and equal access to healthcare in Croatia, Germany, Poland, and Slovenia.MethodsThe data reported come from semi-structured interviews with n = 39 healthcare professionals. The interviews were analyzed using the methods of content analysis and thematic analysis.ResultsRespondents in all four countries acknowledged that socioeconomic factors and membership in a minority group have an impact on access to healthcare services, but its scope varies depending on the country. Underfunding of healthcare, language barriers, inadequate cultural training or lack of interpersonal competencies, and lack of institutional support were presented as major challenges in the provision of diversity-responsive healthcare. The majority of interviewees did not perceive direct systemic exclusion of minority groups; however, they reported cases of individual discrimination through the presence of homophobia or racism.DiscussionTo improve the situation, systemic interventions are needed that encompass all levels of healthcare systems - from policies to addressing existing challenges at the healthcare facility level to improving the attitudes and skills of individual healthcare providers.